Facial Growth in the Rhesus Monkey : A Longitudinal Cephalometric Study - Schneiderman, Emet D. (Book collections on Project MUSE., 2014)
For a wide spectrum of scientists from biomedical and dental researchers to primatologists and physical anthropologists, Emet Schneiderman offers the most accurate and up-to-date presentation of the normal growth of the lower facial skeleton in a primate species. His study is based on a sample of thirty-five captive rhesus monkeys, whose facial growth was traced over a ten-year period spanning from infancy to adulthood. The author identifies the relative contribution of various sites of growth, quantifies the relative roles of different types of development--such as appositional and condyla.